A novel balanced wideband power divider based on microstrip‐slot transitions. Issue 4 (24th October 2013) - Yang, Fan; Wei, Feng; Liu, Shu‐Fang; Shi, Xiao‐Wei
ABSTRACT A novel design of a balanced wideband power divider (PD) with enhanced common‐mode (CM) suppression is proposed. The top and bottom layers of the structure contain tapered microstrip line. Those microstrip lines are coupled via slotline in the ground plane, which is located at the middle layer. With appropriate placement of the slotline, the coupling between the slotline mode and the differential‐mode (DM) signals can be maximized, while that between the slotline mode and the CM signals can be minimized. Simulated and measured results show that the proposed PD has equal power division, low insertion loss, and good return loss. In the measurement, the fractional bandwidth of the measured −10 dB (DM) return loss is about 101% (1.82–5.35 GHz), the insertion loss for the DM signals is less than 5 dB, the suppression of the CM signals is higher than 45 dB, and the DM isolation is better than 10 dB over the fractional bandwidth. © 2013 Wiley Periodicals, Inc. Int J RF and Microwave CAE 24:437–442, 2014.